Photoblastism in Some of the Desert Grass Seeds - Mukherjee, Achala; Chatterji, U N (Annals of Arid Zone, 2016)
The seeds of Cenchrus ciliaris were capable of adaptation to any condition of,sght as regards their germination. The seeds of Panicum antidotale behaved in a nearly similar way to those of Cenchrus ciliaris. 1he seeds of Panicum coloratum were light senstive; those of Panicum turgidum and Cenchrus setigerus preferred comparatively dark conditions. The behaviour of the seeds of Oenchru8 prieurii towards light could not be generalised. but undoubtedly they preferred to germinate in dark under optimum thermal conditions.